Collaborating with the Enemy: Function of Macrophages in the Development of Neoplastic Disease - Andrzej Eljaszewicz; Małgorzata Wiese; Anna Helmin-Basa; Michal Jankowski; Lidia Gackowska; Izabela Kubiszewska; Wojciech Kaszewski; Jacek Michalkiewicz; Wojciech Zegarski (Hindawi Limited, 2013)
Due to the profile of released mediators (such as cytokines, chemokines, growth factors, etc.), neoplastic cells modulate the activity of immune system, directly affecting its components both locally and peripherally. This is reflected by the limited antineoplastic activity of the immune system (immunosuppressive effect), induction of tolerance to neoplastic antigens, and the promotion of processes associated with the proliferation of neoplastic tissue. Most of these responses are macrophages dependent, since these cells show proangiogenic properties, attenuate the adaptive response (anergization of naïve T lymphocytes, induction of Treg cell formation, polarization of immune response towards Th2, etc.), and support invasion and metastases formation. Tumor-associated macrophages (TAMs), a predominant component of leukocytic infiltrate, "cooperate" with the neoplastic tissue, leading to the intensified proliferation and the immune escape of the latter. This paper characterizes the function of macrophages in the development of neoplastic disease.